All-union school of metrical number theory in Palanga - Journal, Lithuanian Mathematical (Lithuanian Mathematical Journal, 1966)
Original title in Russian and Lithuanian: Всесоюзная школа по метрической теории чисел в Паланге Visasąjunginė metrinės skaičių teorijos mokykla Palangoje